Impact of Web-based Case Conferencing on Cancer Genetics Training Outcomes for Community-based Clinicians - Blazer, Kathleen R. (2012)
INTRODUCTION: Technology and market forces are driving the demand for cancer risk assessment services in the community setting, where few clinicians are trained to order and interpret predictive genetic tests. City of Hope conducts a three-phase course in genetic cancer risk assessment (GCRA) for community-based clinicians, comprised of distance didactics, face-to-face workshops and 12 months of professional development. As designed, the course cannot meet increasing demands for GCRA training. Action research identified face-to-face workshops as a barrier to increasing course capacity. This study compared the learning effectiveness of Web-based case conferencing to face-to-face training. METHODS: A quasi-experimental design compared pre-post knowledge, skills and professional self-efficacy outcomes from 2009-2010 course cohorts (n=96). The intervention group (n=52) engaged in Web-based case conferences during distance learning; the comparison group (n=44) participated in the course as originally designed. RESULTS: Both groups and all practice disciplines demonstrated significant pre-to-post increases on all measures. Knowledge increases were higher for the intervention group (p < .015); skills and self-efficacy increases were comparable between groups (p < .33 and p < .30, respectively). DISCUSSION: Findings support the learning utility of Web-based case conferencing. Further studies may inform the development of tools to assess the impact of Web-based case conferencing on practice change and patient outcomes, in alignment with the highest standards of continuing professional development.